Remote Thermal Signature Point Target Acquisition System Using Continuous PID Algorithm and Thermal Image Filtration for UAV Systems - Robert MATYSKO (System namierzania punktowego sygnatury termicznej odległej od otoczenia z wykorzystaniem ciągłego algorytmu PID i filtracji obrazu termowizyjnego dla układów UAV, 2023)
The aspects relating to unmanned aircraft and their target acquisition systems are continuously being developed. The subject of the study is a target acquisition system with a thermal camera. A control system is presented consisting of three subsystems. Open- and closed-loop control systems are used. Experimental results unambiguously show that this is a promising line of research and form the basis for further efforts on the topic.
Keywords: Proces sterowania BSP